The Role of Peer Mentoring in Reducing Dropout Rates and Strengthening Social Support Networks in Universities - Saugadi Saugadi; Mustakim Mustakim; Dalila Bebbouchi (International Forum of Researchers and Lecturers, 2024)
This study explores the role of peer mentoring as a strategy to reduce student dropout rates and strengthen social support networks in universities. Using a mixed-methods approach that combined quantitative surveys and qualitative interviews, the research examined students’ sense of belonging, academic motivation, persistence intention, and access to emotional and academic support. The findings indicate that peer mentoring significantly enhances students’ sense of community, increases their academic motivation, and strengthens their commitment to continue their studies. Compared to other retention strategies such as academic counseling or financial support, peer mentoring provides unique advantages by fostering ongoing peer-to-peer relationships and expanding social networks. Moreover, the study found that mentor–mentee interactions create a safe space for students to share academic challenges, personal concerns, and coping strategies, which contributes to improved well-being and greater confidence in navigating university life. Peer mentoring also offers opportunities for skill development, including communication, collaboration, and self-regulation, making it beneficial not only for mentees but also for mentors. These results suggest that peer mentoring not only mitigates dropout risks but also contributes to building long-term resilience and a supportive learning environment for students. Therefore, universities are encouraged to integrate structured peer mentoring programs into their retention initiatives to promote student success and holistic development.